A didactical engineering for the teaching of enumeration in early-childhood education (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this work, we have developed a small didactic engineering for the learning of enumeration, a "forgotten" mathematical knowledge (for its lack of inclusion in the curriculum of early-childhood education). Specifically, we have designed seven a-didactical situations for the learning of this knowledge with the students of CEIP Julian Picasso de La Bobadilla, 3 and 4 years old. The choice of didactical variables in each of the situations attempts the evolution and adaptation of the strategies carried out by the subjects, linked to the impervious knowledge. After the implementation in the classroom, we analyze the results comparing them with those foreseen in the a priori design. The theoretical framework gives meaning to the whole design, since it includes learning by adaptation to the environment and the Theory of Didactic Situations.
Keywords: Didactical Engineering; A-didactical situation; Enumeration; Early-childhood Education; Theory of Didactical Situations